From Marshall to Keynes : an essay on the monetary theory of the Cambridge school - Eshag, Eprime (Oxford: B. Blackwell, 1963)
This book is divided into two major parts-Monetary theory and Monetary policy. The first part, which is subdivided into three chapters, covers the subjects of the internal and external value of money and the theory of interest. In the second part of the book, under the heading of Monetary Policy, the subjects of the role of money in the economy and of monetary instruments are discussed in two separate chapters.
Bibliographical footnotes.
usc 10/7/17
Loans
Keywords: Money; Currency question; Monetary policy